IMPLEMENTATION OF SELF-REGULATED LEARNING IN INCREASING STUDENT INDEPENDENCE IN ISLAMIC RELIGIOUS EDUCATION LEARNING AT SMK SYAIFUL JAMIL BLEGA BANGKALAN - Hasan, Nur; Amiruddin, Mohammad (LP2M IAI Al-Khairat Pamekasan, 2025)
The implementation of Self-Regulated Learning (SRL) at SMK Syaiful Jamil Blega Bangkalan is applied as a learning method that aims to increase student learning independence, especially in Islamic Religious Education subjects. SRL helps students optimize their cognitive potential through the stages of metacognitive, motivational, and behavioral regulation. However, initial research shows that some students still lack confidence in mastering the material due to low self-awareness, learning motivation, and thinking skills. This is reflected in a less conducive learning atmosphere, failure to complete assignments, and negative behavior in class. Supporting factors for SRL include good lesson plans, prior knowledge provided by teachers, and adequate facilities and infrastructure. The obstacles faced include the lack of student handbooks, unsupportive environment, lack of parental control, and student behavior such as laziness and skipping class. Nevertheless, the implementation of SRL has a positive impact on students' learning independence, such as the ability to organize study schedules, set goals, take responsibility, solve problems, and seek information independently without relying on others. Thus, the emphasis on SRL implementation is expected to form more independent and effective students in the learning process.